What have we learned from the volcanic eruptions in Iceland in 2010 and 2011? - Weinzierl, Bernadett; Diehl, Alexander (DWD, 2014)
Before the eruption of Eyjafjallajökull in spring 2010, volcanic ash was not considered an issue in aviation meteorology in Central Europe. During the Eyjafjallajökull eruption, the prevailing meteorological conditions led to the fast transport of volcanic ash towards Central Europe. The presence of volcanic ash in the airspace over Europe caused very extensive restrictions to aviation which were the logical consequence of international regulations valid at that time. As a consequence of the volcanic eruption in 2010, there was the need to develop new procedures and regulations for an appropriate response to future volcanic eruptions. In this article, we give a retrospective view on the volcanic eruptions in Iceland in 2010 and 2011, present the concept of "Visible Ash" and summarize the national and international progress in the monitoring and forecasting of volcanic ash since 2010.